Novel methods of treating atopic dermatitis - Martyna Choinka; Małgorzata Komarów; Natalia Wdowiak; Karina Lissak; Zuzanna Szczepaniak; Agata Konopka; Jakub Kalisiak; Dominika Karasińska (Nicolaus Copernicus University in Toruń, 2024)
Atopic dermatitis is a long-term inflammatory skin disease caused by factors such as skin barrier dysfunction and immune system dysregulation . Currently, the first-line treatment for atopic dermatitis involves the use of topical glucocorticosteroids; however, this treatment is associated with many side effects.  Therefore the need of finding new methods of treatment arises. Objective: The objective of this study is to gather and analyze literature on new methods of treating atopic dermatitis. Materials and methods: The review was based on the analysis of materials collected in the database, PubMed, Google Scholar, Web of Science, Embaseand, Scopus, books and other scientific articles.